Mathematical modeling for assessing the role of the subway in the transport systems of large cities - N. V. Bulycheva; D. V. Kapski; L. A. Losin (Системный анализ и прикладная информатика, 2022)
In this study, using the model of passenger flow formation on a conditional transport network based on the iterative process of changes in the passenger flows and velocities, the need for high-speed public transport, in particular, the subway, is estimated. The model allows the formation of the route of potential high-speed transport based on the calculated passenger flows. The results of the experiment are presented for the example of the Krasnodar transport system for three periods – 2007, 2017, 2022.